ASN Perceptions and Organizational Framework Model of the Regional Research and Innovation Agency (BRIDA): A Study on Structuring and Formation Processes in Indonesia - Wahyuni Wahyuni; Guntur Fernanto; Yusniah Anggraini; Ray Septianis Kartika (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: Despite the mandate of Presidential Regulation No. 78 of 2021, BRIDA establishment remains uneven across regions due to functional crises and limited innovation-support capacity, resulting in gradual implementation at provincial and local government levels. Objective: This study aims to assess civil servants’ (Aparatur Sipil Negara/ASN) perceptions of the urgency of BRIDAwithin research organizations and to develop a structured organizational framework for its formation. Methods: An exploratory sequential mixed-methods approach was used by distributing questionnaires through Google Forms to 67 ASN from various local governments. The findings show that 54 respondents (81%) acknowledged the urgency of BRIDA, 50 respondents (75%) supported its role in the innovation ecosystem, and 13 respondents (20%) had submitted proposals for BRIDA formation. Results: The formation process remains suboptimal due to incomplete regional participation, limited availability of academic manuscripts, and insufficient support from provincial governments. The recommendations include establishing data collection mechanisms for regions that have not yet implemented BRIDA, mapping functional needs, planning innovation programs, improving communication between central and regional governments, establishing discussion forums and laboratories, and conducting public outreach regarding BRIDA’s duties and functions. Conclusion: The majority of ASN support the establishment of BRIDA to strengthen the regional innovation ecosystem. Nevertheless, several barriers persist, including functional resource crises, insufficient academic manuscripts, and inadequate provincial guidance. The proposed organizational framework incorporates stages ranging from research and development restructuring, proposal preparation, innovation trials, and practical application to monitoring and evaluation mechanisms that ensure effective innovation implementation.